Menumbuh Kembangkan Kemampuan Berpikir Kreatif Matematis Dengan Pendekatan Contextual Teaching And Learning - Evaderika Ayu Artikasari; Abdul Aziz Saefudin (Universitas Nusantara PGRI Kediri, 2017)
Mathematics is very important in the development of modern technology and can not be separated from our daily lives, therefore students need to be prepared to have the ability  creative  thinking of mathematically so students will be easier in solving a problem involving mathematics given the vast utilization of mathematics. Creative students will be able to compete in real life. In an effort to grow the ability, one of the alternatives that can be done is by using contextual teaching and learning approach (CTL). Components of the CTL approach can foster creative thinking skills that contain indicators of originality, fluency, flexibility and elaboration.